PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN IKAN ASIN REMPAH KHAS ACEH DAN INOVASI ALAT PENJEMURAN MODERN DI SEUMATANG MUDA ITAM ACEH TIMUR - Ihsan, Ahmad; mursyidah, mursyidah; Arif, Zainal; Iskandar, Iskandar; Syntia, Rita (Fakultas Teknik, Universitas Samudra, 2024)
Seumatang Muda Itam Village in East Aceh has significant potential in the fisheries sector but faces challenges due to limited processing innovation and low product value. This community service program aims to empower residents by introducing the traditional Acehnese spiced dried fish processing method and innovative modern drying equipment. Through this training, the community's skills and understanding have significantly improved, particularly in processing tenggiri fish. Evaluations show that 78% of participants found the program highly beneficial, with 73% indicating that the modern drying equipment was effective. These results demonstrate that appropriate technology can enhance the quality and market value of dried fish products. The program also opens up broader market opportunities, including through e-commerce, with the expectation of continued positive impacts for the community. These findings serve as a successful model of empowerment through technological innovation and local product processing in coastal areas.